3(4x-17)=3(x+7)

Simple and best practice solution for 3(4x-17)=3(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-17)=3(x+7) equation:


Simplifying
3(4x + -17) = 3(x + 7)

Reorder the terms:
3(-17 + 4x) = 3(x + 7)
(-17 * 3 + 4x * 3) = 3(x + 7)
(-51 + 12x) = 3(x + 7)

Reorder the terms:
-51 + 12x = 3(7 + x)
-51 + 12x = (7 * 3 + x * 3)
-51 + 12x = (21 + 3x)

Solving
-51 + 12x = 21 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-51 + 12x + -3x = 21 + 3x + -3x

Combine like terms: 12x + -3x = 9x
-51 + 9x = 21 + 3x + -3x

Combine like terms: 3x + -3x = 0
-51 + 9x = 21 + 0
-51 + 9x = 21

Add '51' to each side of the equation.
-51 + 51 + 9x = 21 + 51

Combine like terms: -51 + 51 = 0
0 + 9x = 21 + 51
9x = 21 + 51

Combine like terms: 21 + 51 = 72
9x = 72

Divide each side by '9'.
x = 8

Simplifying
x = 8

See similar equations:

| 36x-45= | | -2(-7n+1)=5n-10 | | 46+21=11g | | 10-5m=45 | | 3(5y-5)-4= | | 17-11=2(x-7) | | 0.7t-3.2=1.7 | | h=-16t^2+60t+1 | | 7x+19-4x+4= | | -(3x+2)= | | -2-y=9 | | -105=8x | | 15x^2-x-54=0 | | 9j+2-j=8 | | ln(5)=ln(x+2)-ln(2) | | -6/-6 | | 0.5+6.4=4.9-18 | | 5v=9 | | 5x-16=x+6 | | -9x+5=-103 | | 3.2x+2.6=23 | | AX^2=2AX | | 7(x-3)=3x+15 | | 4(2x-3/4)=53 | | 455=O | | -3/4=c+7/10 | | 444/100-1/12=x | | 95=O | | x/2-6=-4 | | 4+m/5=8 | | 13(ab)= | | 2/3y-1=7 |

Equations solver categories